2016
DOI: 10.1103/physreva.93.052712
|View full text |Cite
|
Sign up to set email alerts
|

Formation of positron-atom bound states in collisions between Rydberg Ps and neutral atoms

Abstract: Predicted twenty years ago, positron binding to neutral atoms has not yet been observed experimentally. A new scheme is proposed to detect positron-atom bound states by colliding Rydberg positronium (Ps) with neutral atoms. Estimates of the charge-transfer reaction cross section are obtained using the first Born approximation for a selection of neutral atom targets and a wide range of incident Ps energies and principal quantum numbers. We also estimate the corresponding Ps ionization cross section. The accurac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 98 publications
(202 reference statements)
0
24
0
Order By: Relevance
“…The Ps TOF distribution is based on one that is measured in a quadrupole guide (see Sect. 5.1), and the cross sections for Ps-Zn scattering have been calculated [476]. These data imply that a discernible loss signal might be observed at Zn pressures close to 1 × 10 −4 mbar, although this could be lowered if slower Ps atoms were used.…”
Section: Scatteringmentioning
confidence: 96%
See 2 more Smart Citations
“…The Ps TOF distribution is based on one that is measured in a quadrupole guide (see Sect. 5.1), and the cross sections for Ps-Zn scattering have been calculated [476]. These data imply that a discernible loss signal might be observed at Zn pressures close to 1 × 10 −4 mbar, although this could be lowered if slower Ps atoms were used.…”
Section: Scatteringmentioning
confidence: 96%
“…There may, however, be some specialist experiments for which it is advantageous to select a slower part of the distribution. For example, this may be the case in experiments designed to produce positron-atom bound states via Rydberg Ps collisions with atoms [476]. Figure 28 shows Rydberg Ps production (a) and transmission (b) in a curved guide, as a function of the IR excitation laser wavelength.…”
Section: Manipulation Of Rydberg Atoms With Electric Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…About 60 positronic molecules have so far been produced from low-energy positron collisions, [18] with lifetimes around 10 À9 seconds (mainly limited by positron detachment accompanied by vibrational de-excitation). Although several schemes have been proposed to detect Ps-atom bound states, [24] the production of positronic atoms remains ac hallenge,with the notable exception of PsH [25] (i.e., the e + + H À compound, denoted here as e + ·H À ). Accurate computational simulations,r ecently reviewed by Gribakin et al [18] and Schrader, [23] have indicated about 10 energetically stable positronic atoms.…”
mentioning
confidence: 99%
“…Indeed, with the addition of extended electrodes simulations suggest that a stronger focusing effect is possible if time-varying fields are used to account for the different Ps velocities [61]. This could be useful in experiments in which Ps atoms interact with other species in order to study scattering or charge exchange mechanisms [62][63][64]. We note that it is difficult to characterize the overall efficiency and acceptance of the guide because we do not accurately know the initial phase-space properties of the Ps atoms.…”
Section: Resultsmentioning
confidence: 99%